The complete chloroplast genome sequence of Huperzia javanica (sw.) C. Y. Yang in Lycopodiaceae - Hong-rui Zhang; Jong-Soo Kang; Ronald L. L. Viane; Xian-Chun Zhang (Mitochondrial DNA. Part B. Resources, 2017)
Huperzia javanica (Sw.) C. Y. Yang is a valuable medical herb used for treating Alzheimer’s disease. Here, we described the complete chloroplast genome of H. javanica using Illumina paired-end sequencing. The total genome length is 154,415 bp, containing 119 unique genes, with 86 protein-coding genes, 29 tRNA genes, and 4 rRNA genes. The gene content and their order are consistent with two previously reported Huperzia genomes. The overall GC content of the chloroplast genome of H. javanica is 36.4%. The topology of our maximum-likelihood tree is consistent with topologies found in previous studies, with H. javanica sister to a clade of H. serrata and H. lucidula. We support the recognition of H. javanica as an independent species. Huperzia serrata is more closely related to H. lucidula than to H. javanica.